Fusarium Wilt of Queen Palm and Mexican Fan Palm - Monica L. Elliott (EDIS)
PP278, a 6-page illustrated fact sheet by Monica L. Elliot, describes this lethal fungal disease affecting primarily queen and Mexican fan palms — pathogen and hosts, symptoms, diagnosis, and disease management. Includes references. Published by the UF Department of Plant Pathology, June 2010.